Correlation of Sperm Parameters with Age and Body Mass Index in Infertile Men - Ali Nasr-Esfahani; Kosar Pashaei; Marziyeh Tavalaee; Paria Behdarvandian; Bahare Nikoozar; Mohammad Hossein Nasr-Esfahani (مجله دانشگاه علوم پزشکی گرگان)
Background and Objective: Obesity and advancing age in men, in addition to numerous health problems, can negatively affect spermatogenesis and fertility potential. The present study aimed to determine the correlation of sperm parameters with age and body mass index (BMI) in infertile men. Methods: In this descriptive-analytical study, semen parameters (concentration, motility, and morphology) of 7069 men referring to an infertility center in Isfahan were evaluated based on the 2010 World Health Organization (WHO) guidelines. BMI was calculated by dividing an individual’s weight (kg) by the square of their height (m). Results: A weak positive correlation was observed between men’s BMI and age (P<0.001, r=0.07). Also semen volume (P<0.001, r=-0.02), sperm concentration (P<0.001, r=-0.02), and sperm count (P<0.001, r=-0.04) had a weak negative correlation with BMI. No statistically significant correlation was observed between sperm motility and BMI. Regarding men’s age, only a weak negative correlation was observed between this parameter and sperm motility (P<0.001, r=-0.04). Conclusion: Increasing BMI and age in men may be associated with decreased sperm quality and fertility potential.